Legal Implication of the Effect of the TRIPS Agreement on the Trade Marks Law in Nigeria - Oloko, Temitope O. (European Scientific Journal, ESJ, 2016)
The implication and the effects of the TRIPS Agreement in developing nations are constantly unfolding. Modern businesses use trade marks as an important public relations tool for marketing purposes. Considering the importance of the TRIPS Agreement in the trade mark regime, assessing the legal effect that the Agreement has on the law in Nigeria helps in determining the compliance of the Trade Mark Law to a large extent. The aim of this article is to identify the areas of compliance and to discuss the diversity and effectiveness of the TRIPS agreement. The article sheds light on the level of compliance of the Trade Marks Law and the expected impact. This could help in identifying the level of fulfilment of Nigeria’s international trade obligation. The study contributes to knowledge by providing insights in determining the extent to which the Trade Mark Law still need reformation. The areas covered by this article are limited to service marks, well-known marks, the requirement for use, and parallel importation.